The Discourse of Resistance Against Patriarchal Culture in Short Stories by Three Balinese Women Writers - Prameswari, Ni Putu Laksmi Mutiara; Banda, Maria Matildis; Putra, I Nyoman Darma (Mudra : jurnal seni budaya, 2025)
This research aims to examine the discourse on Balinese women's resistance against patriarchal culture as reflected in short stories by three Balinese women writers. Short stories by Oka Rusmini, Kadek Sonia Piscayanti, and Devy Gita were analyzed using Sara Mills' theory of feminist critical discourse analysis and Hélène Cixous' feminine writing. This research uses qualitative methods with data collection techniques in the form of literature study. The female characters in these short stories are both positioned as objects and subjects who fight against sexual harassment, domestic burdens, and pseudo identity. However, the writer's position expresses women's rebellion who cut off her legs, decided to become a prostitute, and planned her death. The reader's position then has implications for women's independence as outlined in the short story as women who are independent in the domestic, economic and traditional fields; support the family; and take care of herself and her children after divorce. The objective of this research is to provide inspiring ideas to voice and fight for injustice due to patriarchal culture experienced by Balinese women in particular and Indonesia in general. In addition, this research is also hoped to be a comparison in depicting the insights of women writers' struggles in various different cultural narratives, especially from the perspective of the global south.